Asymptomatic trace and overt proteinuria in high- and lowbody weight individuals: A preliminary report of communitybased epidemiological study - Kei Nakajima; Eiichiro Kanda; Toshitaka Muneyuki; Kaname Suwa (Society of Diabetic Nephropathy Prevention, 2018)
Background: Overt proteinuria (OP), an established risk factor for kidney and cardiovascular disease, is much prevalent in high and low body weight individuals. Objectives: However, it is equivocal whether trace proteinuria (TrP) is also associated with high and low body weight. Therefore, we address this issue in a large epidemiological study. Patients and Methods: Regarding this association, we examined TrP defined as ± by dipstick urinalysis, in comparison with OP (≥+1) using the data of 70 886 apparently healthy Japanese men and women who underwent a checkup in 2008, aged 20-85 years old. Results: The prevalence of TrP, which was slightly but significantly higher (4.1%) on average compared with OP (3.1%), showed a J-shaped relationship against body mass index (BMI). Logistic regression analysis showed that compared to BMI of 21.0-22.9 kg/m2 , other BMI categories except BMI of 19.0-20.9 kg/m2 were significantly associated with TrP, which were not altered after adjustment for relevant confounding factors including age, sex, and pharmacotherapies for hypertension and diabetes. Unlike TrP, OP was not significantly associated with BMI of 23.0-24.9 kg/m2 , a high-normal body weight, although similar trends were observed in the overall relationship between BMI categories and OP. Conclusions: Current study suggests that TrP is also associated with high and low body weight, seemingly like OP. However, the degree and pattern of associations of TrP with BMI may differ from those of OP. Further study is required particularly in terms of fundamental clinical relevance of TrP.